PENINGKATAN KETERAMPILAN GERAK DASAR MELALUI MODIFIKASI PERMAINAN SIRKUIT (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Learning model is utilized to design a plan of teaching. In the learning process Penadidikan physical healthand recreation for the material basis of the motion in Public Elementary School District 02 Cikura Olean Tegalis low under Teaching Mastery criteria, though the teacher tried to teach well. One way that can be done toimprove student learning outcomes learning model created with game modifications circuits. The researchproblem is how efforts to improve student learning outcomes Elementary School third grade Cikura 02. Thepurpose of this research is to find out as modifying the game circuitry improving basic movement skills for gradeIII Elementary School Cikura 02. The research was conducted in the Elementary School District 02 CikuraOlean, the sample in this study was a third-grade students who totaled 35 students. This research is a classaction consisting of four stages: planning, action, observation and reflection. Observational data collectiontechniques in the activity of students in learning basic movement and questionnaires were used to determine the students' response to the motion base model of learning through game modification circuit. Motion analysis ofthe observed data base of students in the first cycle obtained yield was 81.43%, while in the second cycle resultsobtained 87.71%. Observed data psychomotor performance in the first cycle results obtained 81.49% while87.54% in the second cycle, the first cycle for affective gained 82.29% in the second cycle results obtained87.77% and for the observation of cognitive performance is obtained results obtained in the first cycle results79.31%, while in the second cycle results obtained 85.71%. So the average student activity observed in the firstcycle results obtained 81.10%, while in the second cycle results obtained 85.00%. Learning research has beencarried out through 2 cycles increased. 87.70%. From these data an increase of 6.07%. The conclusion of thisstudy is learning basic motor skills through game modification circuit can be used as an alternative learningmodel of physical education and recreation health so as to overcome the shortcomings of existing facilities andinfrastructure in schools and can make learning models that appeal to students so that students are moreenthusiastic about learning.